Constraints Faced by Women Self Help Groups Involved in Dairy Farming from Hingoli District of Maharashtra - Santosh S. Pathade, Manish N. Sawant , N. Ramesh , K. I. Pordhiya and S.M. Sadashive, (Indian Journal of Extension Education, 2017)
The present investigation was carried out to ascertain the perceived constraints faced by women Self Help Groups.The study was carried out in Hingoli, Aundha and Basmat talukas of Hingoli district of Maharashtra with a samplesize of 120 respondents with the help of well structured and pre-tested interview schedule. The data collected weresubjected to statistical analysis and results were interpreted. High cost of feed, high cost of medicines / treatment,non-availability of green fodder, lack of technical guidance, less number of doctors, receiving low price of milk, highcost of high yielding breeds, non-availability of credit, lack of training programmes, higher incidences of diseases,lack of knowledge regarding vaccination and de-worming schedule, inadequate knowledge about feeding, delay inpayments from dairy co-operative societies, low conception rate through A.I., lack of preservation facilities for theirmilk, inadequate knowledge of diseases and their prevention and control, low productivity of local breeds, distantlocation of milk collection centers were the major constraints faced by respondents in dairy farming.